RELEVANSI KONSEP CATUR YUGA DENGAN REALITA BERMASYARAKAT DAN BERNEGARA SAAT INI - Sedia, I Wayan (Jurnal Ilmiah Cakrawarti, 2021)
Catur Yuga is an age division according to the Hindu religion.  Each era has a different character. At the age  of Satya Yoga or Krta Yuga, human being was dominated by truth.  Tapasya become liability in this era, and long-lived human beings and they were lived in harmony. Entering the era of Treta Yoga, humanity has begun to be interested in worldly things, humans began leaving the tapasya. At the time of Dvapara Yuga, bad human traits began to emerge slowly, it can be said between dharma and adharma have the proper tension. Then the era which has the worst character is Kali Yuga. In this era crime was increase highly, the leader is not longer a patron of the people but rather be a thief of the peaple’s rights. Moral and ethical degradation also the spiritual decline in the quality of an indicator this time era. Catur Yuga concept is addressed in the books of the Puranas. Although it seemed like a forecast, but it is worth a careful study. When linked with the reality of state and Indonesian society life these days, it seems that the Yuga concept is not only a forecast, but rather a reality and have to be faced together. Murder, rape, robbery, freesex, drug abuse, cheating politicians, leaders, corruption, a suite  of  bed behavior that dominates the lives of the people of Indonesian in this Kali Yoga. In the Vishnu Purana says things that be done at the time of Kali and brings great reward is with the name of the Lord over  and over again.  While in the Siva Purana advised to read this book wholeheartedly then sameone will be protected from sin and attain Siva consciousnes. By increasing devotion, by doing such as sravanam, kirtanam, smaranam, padasevanam, arcanam, vandanam, dasya, sankhya, and atmanivedanam, hopefully can counteract the bad influence of Kali Yuga